Estimating EMI shielding effectiveness of graphene-polymer composites at elevated temperatures. (14th August 2017) - Jan, Rahim; Saboor, Abdul; Khan, Ahmad Nawaz; Ahmad, Imtiaz
Abstract: Theoretical EMI shielding performance of few layered graphene-thermoplastic polyurethane composite is predicted based on experimental dielectric characteristics. Initially, the EMI shielding effectiveness is estimated for a range of composites based on graphene nanosheets (GNS) volume fraction ( V f ) at room temperature. An overall attenuation of ~2 dB is predicted at the maximum GNS concentration (0.0055 V f ) mainly due to reflection phenomena as a function of frequency (25 kHz–5 MHz). The electrical network formation at 0.0055 V f GNS is evident from the predicted EMI shielding results. The 0.0055 V f GNS-TPU composite is then evaluated for an estimation of EMI shielding effectiveness at elevated temperatures. An increasing trend in EMI shielding effectiveness is predicted as a function of temperature which reaches ~80 dB (25 kHz) at 453 K. Further increase in temperature (463–473 K) takes attenuation to well above 100 dB. The GNS–GNS interaction at elevated temperatures is responsible for the huge attenuation clearly depicted by the reflection phenomena. The attenuation due to absorption phenomena is quite suppressed in the lower frequency with an increasing trend being observed around 5 MHz.